Penyuluhan Manfaat Daun Kelor Pada Lansia Di Dusun Cilawang - Purnama, Rizki; Iga Putri Wulandari; Intan Avlira; Sintia Shinta Dewi; Jesica Saputri; Cindy Amalia Rahmadan; Juwita Anggraini; Adel Fiki Finanda; Elfira Maharani; Ratna Oktavia Ningrum; Noviana Safitri; Sugiarto Sugiarto (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This community service activity aims to increase the knowledge and skills of elderly people in Cilawang Hamlet regarding the use of moringa leaves as herbal ingredients to support health. The problems identified include a low level of understanding about the nutritional content of moringa leaves, the correct processing methods, and the existence of inaccurate traditional beliefs. The outreach was carried out through lectures, discussions, simulations, and demonstrations of processing moringa into tea, powder, and food products, accompanied by educational media such as leaflets, videos, and presentations. The results of the activity showed a significant increase in participants' knowledge, as indicated by an increase in the average pre-test score from 71% to 87% on the post-test, as well as an increase in the elderly's skills in processing moringa leaves hygienically and appropriately. This activity also produced outputs in the form of the formation of village health cadres, the availability of educational media, and increased moringa utilization practices at the household level. The conclusion of this program is that education-based outreach using visual aids and hands-on practice has proven effective in improving health literacy and encouraging the elderly to use moringa leaves as a safe, easily obtainable, and beneficial herbal alternative to support their health.